Model Kepemimpinan Kepala Sekolah Dalam Membangun Kearifan Lokal Di UPT SDN Dagangan - Nuviyah, Yeti; Thohirin, Ahmad; Suyitno, Suyitno (Science and Education Journal (SICEDU), 2026)
This study aims to describe the leadership model of the school principal in building local wisdom at UPT SD Negeri Dagangan, Parengan District, Tuban Regency. The research employed a qualitative approach using a descriptive case study design. The research subjects consisted of the principal, teachers, educational staff, and students, selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation. Data analysis was conducted interactively through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation.The findings reveal that the principal’s leadership plays a significant role in strengthening local wisdom through exemplary behavior, participatory communication, and the development of school culture. Local values such as mutual cooperation, politeness, responsibility, and social awareness are integrated into school policies, learning activities, and daily habits. The leadership model applied is participatory and humanistic, creating a conducive school climate and strengthening character education. This study concludes that leadership based on local wisdom contributes positively to the development of school culture and students’ character formation. The results of this study are expected to serve as a reference for the development of local wisdom–based educational leadership in primary education institutions..